First-line talazoparib with enzalutamide in HRR-deficient metastatic castration-resistant prostate cancer: the phase 3 TALAPRO-2 trial - Fizazi, Karim; Azad, Arun A.; Matsubara, Nobuaki; Carles, Joan; Fay, Andre P.; Giorgi, Ugo de; Joung, Jae Young; Fong, Peter C. C.; Voog, Eric; Jones, Robert J.; Shore, Neal D.; Dunshee, Curtis; et al. (Nature medicine, 2024)
Preclinical evidence has suggested an interplay between the androgen receptor, which largely drives the growth of prostate cancer cells, and poly(ADP-ribose) polymerase. This association provides a rationale for their co-inhibition for the treatment of metastatic castration-resistant prostate cancer (mCRPC), an area of unmet medical need. The phase 3 TALAPRO-2 study investigated combining the poly(ADP-ribose) polymerase inhibitor talazoparib with enzalutamide versus enzalutamide alone as first-line treatment of mCRPC. Patients were prospectively assessed for tumor alterations in DNA damage response genes involved in homologous recombination repair (HRR). Two cohorts were enrolled sequentially: an all-comers cohort that was enrolled first (cohort 1; N = 805 (169 were HRR-deficient)), followed by an HRR-deficient-only cohort (cohort 2; N = 230). We present results from the alpha-controlled primary analysis for the combined HRR-deficient population (N = 399). Patients were randomized in a 1:1 ratio to talazoparib or placebo, plus enzalutamide. The primary endpoint, radiographic progression-free survival, was met (median not reached at the time of the analysis for the talazoparib group versus 13.8 months for the placebo group; hazard ratio, 0.45; 95% confidence interval, 0.33 to 0.61; P < 0.0001). Data for overall survival, a key secondary endpoint, are immature but favor talazoparib (hazard ratio, 0.69; 95% confidence interval, 0.46 to 1.03; P = 0.07). Common adverse events in the talazoparib group were anemia, fatigue and neutropenia. Combining talazoparib with enzalutamide significantly improved radiographic progression-free survival in patients with mCRPC harboring HRR gene alterations, supporting talazoparib plus enzalutamide as a potential first-line treatment for these patients. ClinicalTrials.gov Identifier: NCT03395197.